2017
DOI: 10.1055/s-0042-122010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the 2015 AGA guidelines on pancreatic cystic neoplasms in a large surgically confirmed multicenter cohort

Abstract: Absract Background and study aims The American Gastroenterological Association (AGA) recently published guidelines for the management of asymptomatic pancreatic cystic neoplasms (PCNs). We aimed to evaluate the diagnostic characteristics of the AGA guidelines in appropriately recommending surgery for malignant PCNs. Patients and methods A retrospective multicenter study was performed of patients who underwent endoscopic ultrasound (EUS) for evaluation of PCNs who ultimately underwent surgical resection from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
(52 reference statements)
0
13
0
1
Order By: Relevance
“…Similar results were provided by Ge et al in a multicenter study of 300 patients with PCNs (including 198 IPMNs), where retrospective application of the AGA guidelines had 83.3% sensitivity and 69.1% specificity for malignancy. Although the guidelines accurately recommended surveillance in 95% of patients, nine invasive cancers (5%) would have been missed 28 . If retrospectively applied to our subgroup of operated patients, the AGA guidelines would not have spared the two patients with low-/intermediate-grade dysplasia from overtreatment because of the copresence of mural nodule and cyst size ≥3 cm in one case and symptoms (acute pancreatitis) in the other.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were provided by Ge et al in a multicenter study of 300 patients with PCNs (including 198 IPMNs), where retrospective application of the AGA guidelines had 83.3% sensitivity and 69.1% specificity for malignancy. Although the guidelines accurately recommended surveillance in 95% of patients, nine invasive cancers (5%) would have been missed 28 . If retrospectively applied to our subgroup of operated patients, the AGA guidelines would not have spared the two patients with low-/intermediate-grade dysplasia from overtreatment because of the copresence of mural nodule and cyst size ≥3 cm in one case and symptoms (acute pancreatitis) in the other.…”
Section: Discussionmentioning
confidence: 99%
“…All the 8 studies were retrospective cohort studies; they included 2 multicenter studies and 6 single-center studies. Seven studies were from the United States and one study was from Japan [ 18 - 25 ]. The quality of the studies was assessed using the Newcastle-Ottawa scale and is reported in .…”
Section: Resultsmentioning
confidence: 99%
“…Among these, Kohli et al [ 20 ], Sighinolfi et al [ 23 ] and Imbe et al [ 19 ] reported the location of the cyst, most commonly in the head of the pancreas (39.5%). The diagnosis of advanced neoplasia was made based on a histological evaluation of resected pancreas [ 18 , 21 , 23 ], cytological analysis of cells aspirated from pancreatic cysts [ 20 , 24 ], or a combination of the two [ 22 ]. Singhi et al also performed molecular testing on aspirated pancreatic cyst fluid to assess mutations in KRAS , GNAS , VHL , TP53 , PIK3CA , and PTEN genes [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, interpreting the results of these sophisticated modalities (e.g. endoscopic ultrasound or magnetic resonance imaging) requires expertise, and the diagnostic performance of the guidelines was reported to be varied in distinguishing benign IPMN and IPMC (sensitivity range from 7.3 to 83.3% and specificity range from 35.2 to 88.2%) (6)(7)(8)(9)(10). Regarding concomitant PDAC, little evidence exists for a screening program.…”
mentioning
confidence: 99%